2013
DOI: 10.2139/ssrn.2335314
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition Finance and Market Timing

Abstract: Bidders have an incentive to pay with stock when their shares are overvalued, but target firms should be reluctant to accept such overvalued payment. In a sample of 2,978 acquisitions, we find that stock payment is readily accepted only when the bidder can justify the financing decision in terms of such economic fundamentals as optimal capital structure. Yet even when the fundamentals justify stock payment, paying with cash is common. In that way, firms can preclude paying with undervalued stock and are more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…In the first case, where the motives are financial, a firm may undertake an M&A activity to adjust to the target capital structure by targeting a firm and absorbing the debt and equity of the acquired firm (Gugler and Konrad, 2002). Vermaelen and Xu (2012) found that 80% of their M&A sample firms out of 3,097, came closer to their target leverage, which was predicted by using Kayhan and Titman (2007) model, following the M&A. Yang (2011) states that most of the M&A decisions narrowed the gap between actual and target leverage ratios after the M&A.…”
Section: Introductionmentioning
confidence: 92%
“…In the first case, where the motives are financial, a firm may undertake an M&A activity to adjust to the target capital structure by targeting a firm and absorbing the debt and equity of the acquired firm (Gugler and Konrad, 2002). Vermaelen and Xu (2012) found that 80% of their M&A sample firms out of 3,097, came closer to their target leverage, which was predicted by using Kayhan and Titman (2007) model, following the M&A. Yang (2011) states that most of the M&A decisions narrowed the gap between actual and target leverage ratios after the M&A.…”
Section: Introductionmentioning
confidence: 92%
“…Many empirical studies have focused on the alternative financing sources and methods of payment in corporate takeovers. In most research (Faccio, Masulis 2005;Harford et al 2009;Vermaelen, Xu 2014), the 'method of payment' is used as synonymous with the 'sources of takeover financing'. Bessler, Drobetz and Zimmermann (2011) argue that the method of payment and the sources of financing are independent of each other and thus should be treated and analyzed separately as well as jointly.…”
Section: Financing Decisionsmentioning
confidence: 99%
“…I repeat the Mahalanobis matching technique as described above and match stock with cash acquirers based on variables including cash to total assets, return on equity, sales growth, the debt‐to‐equity ratio, the price‐to‐earnings ratio, total assets, bidder performance in the year prior to the acquisition, the standard deviation of bidder daily returns in the year prior to the acquisition, the relative size of the deal measured as the deal value over the market value of the bidder's equity, the market‐to‐book value ratio of the bidder as measured 42 days prior to the acquisition, and the actual level of debt. Vermaelen and Xu () and Uysal () show that the capital structure of the firm matters in the acquisition decision process. Pinkowitz, Sturgess, and Williamson () argue that cash rich firms are less likely to employ cash than stock takeovers.…”
Section: Are Stock Acquirers Comparable To Cash Acquirers?mentioning
confidence: 99%